ASSESSMENT OF MEDICINAL PLANTS POTENTIAL OF THE KORUP FOREST THAT ARE USED BY TRADITIONAL HEALERS FOR THE CURE OF TUBERCULOSIS, MALARIA AND OTHER HIV AND AID RELATED DISEASES. MUNDEMBA, S.W. CAMEROON - Fuashi, N. A.; Moua, I. S. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The tropical region and Africa in particular is endowed with an enormous wealth of plant resources. The aim of this study was to assess the medicinal plants potentials of Korup National Park that are used by traditional healers of the Oroko, Korup, and the Ejagham tribes for the cure of tuberculosis, malaria and other HIV and AIDS related diseases. This has complemented the existing Biological data of the Park for the elaboration of participatory management strategies that has promoted the conservation of the Korup National Park amongst stakeholders. For this study to achieve its aim, it elaborated a series of objectives and sub objectives that were considered at the field level as activities and sub-activities. The study made use of existing Biological data of the Korup Forest Dynamic Plot (KFDP). This was complemented by the use of Participatory Rural Appraisal (PRA) tools, questionnaires, visual assessment and direct observation to gather both quantitative and qualitative data for analysis. This was carried out over a one-year period and over two seasons for the collection of meaningful data that were analyzed using appropriate statistical package. The results thereof showed that 13 plant species and 47 plant parts consisting of leaves, roots, sap, fruits, flowers, nuts, oil, backs, and fibres combined in various forms for the cure of tuberculosis, malaria and other HIV and AIDS related diseases. Chemical extracts and the identification of chemical compounds these plant parts are still being awaited.